Analysis of Juridical Concerning Non-Tariff Barriers Indications Against Ministerial Energy and Mineral Resources Decree No. 7 year 2012 about the Increase in Mineral Added Value Through the Mineral Processing and Refining Activity - Agi Gilang Pratama, Joko Priyono, Nanik Prihastuti (Diponegoro Law Journal, 2013)
Since the enactment of Indonesia Act No. 4 in 2009 about Mineral and Coal Mining (UU Minerba), there has been an increase in raw mineral export up to 800%. Most of the exported minerals are raw material or ore. To stop the export rate from getting higher, the government has issued a trade regulation about mineral export and processing or refining in domestic mining field. Government efforts in managing the domestic mineral export indicated an effort to hamper the international trade. The indication of whether there will be an obstruction or not in Indonesia government’s regulation will be discussed through normative juridical approach by doing a review toward mineral trade regulations in Indonesia, based on trade principals and GATT/WTO regulations. Data collections were done by literature study and the analysis method was qualitative. Indonesia government through the Ministry of Trading and the Ministry of Energy and Natural Resources released a ministerial regulation No.7 Year 2012 about the Increase in Mineral Added Value Through the Mineral Processing and Refining Activity as an implementing regulation from the provision in UU Minerba. The mineral importing countries suspected the ministerial regulation as a non-fare obstacle, which is contradicting the GATT/WTO regulations. This obstacle could be seen from the articles in Trade Ministerial Regulation Number 29/M-DAG/PER/5/2012 about the Provisions of Mining Export, and Energy and Natural Resources Ministerial Regulation Number 7 Year 2012 about the Increase in Mineral Added Value Through the Mineral Processing and Refining Activity. In that regulation, the government restricted all the raw minerals or ore export in 2014.  Before the restriction valid, only the corporations registered as ET-Produk Pertambangan  in Commerce Ministry that can do the raw mineral export.